2016
DOI: 10.1007/s00125-015-3854-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hormonal response to intermittent high-intensity and continuous moderate intensity exercise in individuals with type 1 diabetes: a randomised crossover study

Abstract: Aims/hypothesis To investigate exercise-related fuel metabolism in intermittent high-intensity (IHE) and continuous moderate intensity (CONT) exercise in individuals with type 1 diabetes mellitus. Methods In a prospective randomised open-label cross-over trial twelve male individuals with well-controlled type 1 diabetes underwent a 90 min iso-energetic cycling session at 50% maximal oxygen consumption (V ⋅ O 2max ), with (IHE) or without (CONT) interspersed 10 s sprints every 10 min without insulin adaptation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 41 publications
6
57
0
3
Order By: Relevance
“…Nevertheless, in our study, we observed similar SG values during the first 24 hours post‐MVE, as mean SG levels (TT#1 and TT#2) were 143 mg/dL for CSII and 137 mg/dL for MDI‐treated patients. These mean SG levels were comparable to previous studies reporting a mean of approximately 8 mM SG after iso‐energetic exercise (50% of VO 2 max) or of 8 mM SG after MVE, but were lower than other reports achieving levels of up to 9 mM SG after exercise with or without preemptive insulin changes, although definitive conclusions are difficult to draw while comparing our results with these adult cohorts.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, in our study, we observed similar SG values during the first 24 hours post‐MVE, as mean SG levels (TT#1 and TT#2) were 143 mg/dL for CSII and 137 mg/dL for MDI‐treated patients. These mean SG levels were comparable to previous studies reporting a mean of approximately 8 mM SG after iso‐energetic exercise (50% of VO 2 max) or of 8 mM SG after MVE, but were lower than other reports achieving levels of up to 9 mM SG after exercise with or without preemptive insulin changes, although definitive conclusions are difficult to draw while comparing our results with these adult cohorts.…”
Section: Discussionsupporting
confidence: 80%
“…On the contrary, we want to evaluate the impact, in terms of safety and performance, of a protocol that sets forth insulin dosage along with carbohydrate intake diet modifications, compared with usual-care recommendations stated by guidelines for standard of care. This being said, it is worth adding that other trials [2, 10, 11] have evaluated the response of subjects to the 4-step method, so we would be increasing knowledge of this particular intervention.…”
Section: Methodsmentioning
confidence: 99%
“…A clinical trial comparing continuous with intermittent physical activity in subjects with T1D showed that a lower amount of exogenous carbohydrate is required to maintain euglycemia during intermittent compared with continuous activity, and this finding was not related to increased hepatic glucose output but to significantly lower glucose disposal in intermittent compared with continuous activity. Metabolically, this was paralleled by increased levels of counter-regulatory hormones (mainly growth hormone and catecholamines), and substantially higher levels of lactate in intermittent activity [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Esta mesma técnica, aplicada em pacientes adultos, demonstrou menor risco de hipoglicemia pós exercício, aumento da secreção do hormônio do crescimento, catecolameninas e lactato quando utilizadas atividades físicas intervaladas ao invés de atividades continuadas. 13 O exercício físico altera as vias do metabolismo melhorando o controle, porém vários fatores precisam ser avaliados durante todo o processo a fim de evitar a hiperglicemia que pode ocorrer após exercícios intensos e vigorosos ou hipoglicemia, que é mais comum em exercícios mais longos e moderados. 11 Sprints apresentam efeito estabilizador da glicose, porém necessita de adaptação de insulina para previnir hipoglicemias.…”
Section: Considerações Finaisunclassified
“…Comparando o resultado de exercícios intermitentes de alta intensidade e exercícios moderados contínuos, por ensaio clínico prospectivo randomizado e aberto, foram identificados níveis semelhantes de produção de glicose hapática, porém a eliminação da glicose foi significativamente menor no grupo que realizou sprints. 13 Nos adolescentes existe uma estreita relação entre os níveis eleveados de hemoglobina glicosilada (HbA1c) e sobrepeso ou obesidade. 12 Porém, não há comprovação de que o exercício físico melhore os níveis de hemoglobina glicosildada, mas sabe-se que em indivíduos ativos a morbimortalidade diminui independente do resultado da HbA1c.…”
Section: Considerações Finaisunclassified